The disproportion of the dominant and ancillary extremities in displaying movement frequency among young basketball players - Cvorovic, A.; Kocic, M.; Beric, D. (Facta Universitatis: Series Physical Education and Sport, 2011)
Disproportion is an omnipresent occurrence typical for both man and the natural world. Everything that is not identical on both sides of its axis can be considered disproportionate. Basketball is comprised of the following activities: running, jumping, changes of direction, abrupt stops, dribbling, passes, shooting, etc. All of the mentioned activities represent an essential part of the game but with all of them there is a tendency towards the disproportionate use of the extremities, so the left and the right sides of the body are employed differently. The aim of this research was to determine mutual disproportion, which occurs as the consequence of the quality of life and the sport the examinees play. One of the key things was finding out all the possible differences among the three age categories, that is, among the relevant variables and the extent to which they are manifested. A total of 64 young basketball players took part in the research. They were divided into three age groups according to the propositions of the Serbian Basketball Association. The set of measuring instruments comes from the anthropometric (body height - AVIS and body mass - AMAS) and the motor (leg movement frequency, dominant and ancillary - TAPND and TAPNN and hand movement frequency, dominant and ancillary - TAPRD and TAPRN) space and the participants had to fill in a questionnaire, the function of which was to determine their dominant extremity on the grounds of the answers given. A formula for calculating the disproportion coefficient (Jatrjembskaia & Titov, 1999) was used in this research for all the measured variables related to the extremities. The formula is as follows: AS=D - ND/Dx100. Along with the given formula which was used for determining the mutual relationship between the dominant and ancillary parts of the body, another formula which unified all the relevant variables was used: AS(n)= Sigma AS/n. The methods used from the field of comparative statistics were: the T-test and the variance analysis (ANOVA), and in the post-hoc analysis the Tukey test was used. The results show the anticipated differences in the movement frequency of the dominant upper and lower extremities.